The Lyotard dictionary - Sim, Stuart (Edinburgh University Press, 2011)
The first dictionary dedicated to the work of Jean-FranÃʹois Lyotard. Drawing on a multidisciplinary team of experts, the 168 entries in The Lyotard Dictionary explain all of his main concepts, contextualising these within his work as a whole and relating him to his contemporaries. 118 entries cover all of Lyotard's concepts and concerns, from 'Addressee' and 'Aesthetics', through 'I don't know what' and 'Is it happening?' to 'Unpresentable' and 'Writing' A further 50 'linking' entries contextualise Lyotard within the wider intellectual currents of his time, from concepts such as Nazism and Memory to thinkers from Aristotle to Jean Baudrillard Jean-FranÃʹois Lyotard's postmodern thought is massively influential across a host of academic disciplines, from philosophy and the social sciences through to literary, media, and cultural studies.